GREEN HRM PRACTICES AND EMPLOYEE PRO ENVIRONMENTAL BEHAVIOR: ACROSS EMERGING ECONOMIES - Mertayasa, I Gede Agus; Edy, Raden Agus Sarwa; Putra, Putu Steven Eka; Sukmana, IWK Teja; Suartana , I Ketut (Penelitian dan Pengembangan Ilmu, 2025)
This study presents a systematic literature review (SLR) on Green Human Resource Management (Green HRM) practices and their influence on Employee Pro-Environmental Behavior (EPEB) within the context of emerging economies. By analyzing 30 articles meeting the inclusion criteria from Scopus and Web of Science databases between 2012-2024, this study aims to identify publication trends, author affiliation distribution, dominant research methods, journal database sources, and the theories employed. The results indicate a significant increase in publications related to Green HRM and EPEB, especially since 2020, with research predominantly originating from China and Malaysia. Quantitative survey-based methods are the most frequently used approach, and Social Identity Theory/Organizational Identification and the Theory of Planned Behavior (TPB) are the most adopted theoretical frameworks. The findings suggest that Green HRM practices, such as green recruitment, environmental training, sustainability-oriented performance appraisals, and reward systems, effectively foster EPEB. This research contributes theoretically by expanding the understanding of Green HRM in emerging economies and provides a foundation for further empirical studies. Practically, these results offer guidance for HR managers to implement green HRM strategies that can enhance employee engagement and organizational sustainability performance. Study limitations include English language restriction and database coverage, leading to recommendations for future multi-country research, exploration of mediating/moderating variables, focus on specific industry contexts, and the use of longitudinal approaches.